Entrepreneurial Barriers that are Confronted by Entrepreneurs Living with Physical Disabilities: A Thematic Analysis - Eugine Tafadzwa Maziriri; Welcome Madinga; Thobekani Lose (Journal of Economics and Behavioral Studies, 2017)
Living with a physical disability can interfere with an individual’s ability to participate actively in economic and social life. It is imperative to comprehensively understand the entrepreneurial barriers hindering the development of entrepreneurs living with physical disabilities. In spite of the increasing research on entrepreneurship, there seems to be a paucity of studies that have investigated the entrepreneurial barriers that are faced by entrepreneurs living with physical disabilities in South Africa. This study set out to explore the entrepreneurial barriers that are confronted by entrepreneurs living with physical disabilities. In this study, data were collected within the Sebokeng Township, which is an African township located in the Vaal Triangle, south of Johannesburg in South Africa. A qualitative research approach was used to collect data for the study. The researchers gathered qualitative data by means of semi-structured face-to-face interviews and focus groups. The analysis of the qualitative data was conducted through the use of thematic analysis. The themes that emerged from the findings include lack of equipment and machinery, discrimination, business networking, hardships in obtaining start-up capital, knowledge of support centres for entrepreneurs living with physical disabilities, and lack of education and training. Each theme was discussed individually, followed by substantiating quotes. Most respondents stressed that the barriers they face hinder the survival and growth of their ventures. The paper suggested that in order to help entrepreneurs living with physical disabilities, the South African government must formulate some schemes that are most necessary for their improvement and betterment of their life.